Pengembangan Sistem Informasi Perpustakaan menggunakan Metode Extreme Programming (Studi pada: SMK 1 Muhammadiyah Malang) - Rizky Edyatna Putra; Satrio Agung Wicaksono; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
SMK 1 Muhammadiyah Malang has a school library that provides a collection of books and various magazines to be used as learning media by students and teachers in schools. At present, libraries still use bookkeeping systems to service book lending and book return services. The library officer records all service activities that have been carried out on a striped folio book, so that the officer spends a lot of time doing book lending and returning books, as well as automatic processing of fines. The library officer also records again for making a book loan transaction report and returning the book. So this research is done by developing a library information system that can overcome the problem of time efficiency when borrowing books, returning books, processing fines and making transaction reports. The research method used in this study is the Extreme Programming (XP) method in developing library information systems to be built and using the Unified Modeling Language (UML) modeling language to facilitate the design of the system to be built. Implementation system will use the C-Sharp programming language (C#). Based on the problem analysis carried out using the interview method, it produces 8 (eight) features and 10 (ten) functional requirements. The white-box testing and black-box testing test results are valid, which means the system can run properly according to the desired needs. The test results of User Acceptance Testing (UAT) indicate that the system is 100% acceptable and is suitable for use by users, namely library officers.